Makna Simbolis Gamelan Kodhok Ngorek Di Keraton Surakarta - Panggiyo Panggiyo (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2008)
Speaking about gamelan Kodok Ngorek is in fact speaking about traditional Javanese culture. The palace as development of Javanese culture centre. Many kind of culture product many years a go, is afull symbolical. So that, I try to get a meaningKeyword : by to sharp analyce and deep mind method